PENGARUH MODEL PROJECT-BASED LEARNING DAN KECERDASAN EMOSIONAL TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS V SEKOLAH DASAR NEGERI - Kartika Dwi Anggraeni; Tri Dyah Prastiti; Happy Karlina Marjo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to examine the influence of the Project-Based Learning (PjBL) model and emotional intelligence on the mathematics learning outcomes of fifth-grade students at Sekolah Dasar Negeri. The research method used is experimental with a post-test only control group design. The research subjects are fifth-grade students at SDN Ki Hajar Dewantara, Cilincing District. The research instruments include mathematics learning outcomes tests and emotional intelligence questionnaires. Data analysis was performed using t-tests and multiple regression. The results show that the PjBL model and emotional intelligence significantly affect students' mathematics learning outcomes.